Ozone therapy in the rehabilitation of Bell's facial paralysis. Case series (Ozone Therapy Global Journal, 2019)
Introduction: Bell's palsy is an everyday condition of generally idiopathic etiology, which involves the facial nerve causing alteration in muscle responses, as well as psychological and social interaction problems. Therefore, seeking increasingly effective treatments is of vital importance. Ozone therapy is a treatment that does not cause side effects, allergies, interaction with other drugs, is easy to apply and low cost which makes it an excellent therapy. Objective: To present four clinical cases in which ozone therapy was used as a second-choice treatment in Bell's palsy after the symptoms had appeared and without having used any treatment, either antiviral, corticosteroids of first choice or not having completed it.Conclusion: Ozone therapy as a treatment in Bell's palsy was effective in the four clinical cases, finding improvement from the first session, regardless of the time of evolution.